Cover, Content, and Editorial Note from J Mol Docking Vol. 2 No. 1 June 2022 - Chief Editor of J Mol Docking (Journal of Molecular Docking, 2022)
Assalamu’alaikum Wr. Wb. Alhamdulillahirabbil ‘alamin. After a long wait of almost 1 year from the first planned, finally, the new scientific journal of the Department of Pharmacy Universitas Muhammadiyah Palangkaraya can be published. This scientific journal was named Journal of Molecular Docking (J Mol Docking), inspired by one of the most popular in silico methods in computer-aided drug design. Journal of Molecular Docking is published every 6 months (2 issues/year) every June and December. This edition contains five articles consisting of writings from three countries, including India, Mexico, and Nigeria. The authors come from several institutions, including Maulana Azad National Urdu University, Osmania University, Osmania University College for Women, Vignan's Foundation for Science, Technology & Research, Ahmadu Bello University, Benemérita Universidad Autónoma de Puebla, Universidad Autónoma de Guerrero, The Tamil Nadu Dr. M.G.R. Medical University, and Anna University. Editorial boards are fully aware that this edition has room for improvement. Hence with all humility, willing to accept constructive suggestions and feedback for improvements to the publication for the next editions. The editorial board would like to thank all editors and reviewers, and contributors of the scientific articles who have provided the repertoire in this issue. We hope that all parties, especially the contributors of the articles, can re-participate for publication in the next edition on December 2022. Wassalamu’alaikum Wr. Wb.